Effect of alternate culture yoghurt and straining periods on textural and sensory attributes of Greek yoghurts made using buffalo milk - Desai, Rachana; V., Sreeja (Indian Journal of Dairy Science, 2022)
Sensory and textural attributes of probiotic Greek yoghurts prepared using alternate culture yoghurt and a commercial yoghurt culture at different straining periods were studied.Â Greek yoghurts were prepared from buffalo milk using alternate culture yoghurt C1 (Streptococcus thermophilus MTCC 5460 +Lactobacillus helveticus MTCC 5463) and C2 (MTCC 5460 + Lb. rhamnosus MTCC 5946) and a commercial yoghurt culture C3 (S. thermophilus + Lb. bulgaricus). Between the two alternate cultures, Greek yoghurt of C1 was found to be superior in sensory attributes. Hence, in the further study, C1 and C3 were used for the preparation of products using different straining periods (30min, 75min, and 105min) to obtain final total solids of 21%, 23% and 25%. Greek yoghurts were evaluated for sensory, physico-chemical, microbiological and textural characteristics. Greek yoghurt prepared using C1 and a straining period of 105 min exhibited superior sensory and textural attributes. The product scored highest for body and texture characteristics and its overall acceptability was judged as the best. It also showed higher values of hardness, cohesiveness in comparison to product of C3. With increasing periods of straining, the hardness, cohesiveness and adhesiveness of the Greek yoghurts increased. The mean culture count of the products varied between 8 to 9 log CFU/g. Results indicated that alternate culture yoghurt comprising of Streptococcus thermophilus MTCC 5460 and Lactobacillus helveticus MTCC 5463 can be successfully used for the preparation of Greek yoghurts from buffalo milk.